Analisis Kesulitan Belajar Siswa Kelas II UPTD SDN Tanjung Jati 2 pada Materi Penjumlahan dan Pengurangan - Ilmiyah Ilmi; Agung Setyawan; Sih Widayati (Citra Dharma Cindekia, 2024)
This research aims to examine the learning difficulties experienced by class II students at SDN Tanjung Jati 2 in addition and subtraction material. This research focuses on identifying various factors that influence learning difficulties, including cognitive aspects, environment, teaching methods, and emotional factors. The approach used is qualitative, through observation, interviews with teachers, and analysis of student learning outcomes. The research results revealed that a lack of understanding of basic mathematical concepts, weak short-term memory, lack of support from family, and teaching methods that tend to be conventional are the main causes that hinder students from learning addition and subtraction. Apart from that, anxiety when facing mathematics assignments also affects students' learning motivation. This research recommends developing more interactive teaching methods, increasing family involvement in the student learning process, and using more interesting teaching aids in schools. The implementation of these strategies is expected to help students overcome learning difficulties and improve their understanding of basic mathematical concepts.